2020
DOI: 10.1002/mus.27135
|View full text |Cite
|
Sign up to set email alerts
|

Positive ice pack test in a patient with Lambert‐Eaton myasthenic syndrome

Abstract: In contrast to myasthenia gravis, ptosis is usually a late manifestation in LEMS, but there are recent case reports of pure ocular LEMS. 8 Oculobulbar symptoms at presentation occur in only 5% of patients with LEMS, as compared to 90% of those with myasthenia gravis, but are found in approximately 30% by 3 mo and 50% by 12 mo. 9 There are reports of the ice pack test being positive in patients with ptosis secondary to the cosmetic use of botulinum toxin type A. 10 Here, an ice pack test resulted in improvement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…There were 2 recent interesting case reports on this topic. Awatare et al 30 reported a 72-year-old man with a one-year history of gradually progressive difficulty climbing stairs and standing up from a seated position. He had constipation, dry mouth, and erectile dysfunction.…”
Section: Lambert–eaton Myasthenic Syndromementioning
confidence: 99%
See 1 more Smart Citation
“…There were 2 recent interesting case reports on this topic. Awatare et al 30 reported a 72-year-old man with a one-year history of gradually progressive difficulty climbing stairs and standing up from a seated position. He had constipation, dry mouth, and erectile dysfunction.…”
Section: Lambert–eaton Myasthenic Syndromementioning
confidence: 99%
“…This case report nicely illustrates that the ice pack test can be positive in LEMS. 30 Its overall sensitivity in LEMS is unknown, and ptosis may not be very prominent with LEMS. The ice pack test is reported to be sensitive in about 77% with MG with a specificity of 98%.…”
Section: Lambert–eaton Myasthenic Syndromementioning
confidence: 99%